2023
DOI: 10.1002/brb3.3339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light therapy on depression and sleep in women during pregnancy or the postpartum period: A systematic review and meta‐analysis

Xinyu Li,
Liang Fang,
Lianzi Guan
et al.

Abstract: BackgroundIn recent years, light therapy has been tried for the treatment of depression and sleep in pregnancy or postnatal period women, but the results have been inconclusive. This meta‐analysis is the first to systematically review the effects of light therapy on depression and sleep disturbances in women during pregnancy and the postnatal period.MethodsWe searched for randomized controlled studies in PubMed, Embase, Cochrane Library, Web of Science, Chinese National Knowledge Infrastructure, and Chinese Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Skin-to-skin contact, which is associated with improved short-term and long-term outcomes for both birthing individuals and the infants born at term, 2 has been shown to reduce preterm infant death and to enhance normal neurodevelopment. 3 In addition, kangaroo mother care has been shown in several studies to reduce maternal morbidity, including postpartum depression, both in high-and low-income countries. A study in high-income settings showed that intermittent skin-to-skin contact for 1 to 2 hours per day reduced depression scores in the first month after delivery.…”
Section: Screening Recommendations and Treatments For Postpartum Depr...mentioning
confidence: 99%
“…Skin-to-skin contact, which is associated with improved short-term and long-term outcomes for both birthing individuals and the infants born at term, 2 has been shown to reduce preterm infant death and to enhance normal neurodevelopment. 3 In addition, kangaroo mother care has been shown in several studies to reduce maternal morbidity, including postpartum depression, both in high-and low-income countries. A study in high-income settings showed that intermittent skin-to-skin contact for 1 to 2 hours per day reduced depression scores in the first month after delivery.…”
Section: Screening Recommendations and Treatments For Postpartum Depr...mentioning
confidence: 99%
“…A meta-analysis of 8 studies found a mild to moderate effect on perinatal depression symptoms. 3 In peer support, a peer who has experienced a mental health challenge supports a postpartum individual by providing psychoeducation, recovery planning and goal setting, support in navigating the mental health system, and practical tools to manage mental health symptoms and parenting. Peer support has also been associated with lower symptoms of postpartum depression.…”
Section: Screening Recommendations and Treatments For Postpartum Depr...mentioning
confidence: 99%